Predictive Evolution Factors of Incidentally Discovered Suspected Low-Grade Gliomas: Results From a Consecutive Series of 101 Patients. Issue 4 (28th December 2020) - Boetto, Julien; Ng, Sam; Duffau, Hugues
Abstract: BACKGROUND: Incidentally discovered suspected diffuse low-grade gliomas (LGGs) on brain imaging pose a challenge to neurosurgeons. Modern surgical series of LGGs favor early prophylactic surgery with a maximal extent of resection. However, some nonevolutive lesions may mimic LGGs on magnetic resonance imaging (MRI). OBJECTIVE: To determine objective criteria to advocate surgical resection of an incidentally discovered suspected LGG based upon MRI findings. METHODS: The prospective cohort of patients referred to our institution for an incidental finding suggestive of LGG was retrospectively reviewed. Stable lesions underwent systematic serial MRI follow-up, while evolutive lesions underwent prophylactic surgery under awake conditions. Initial clinico-radiological features were compared between stable and evolutive lesions in order to determine predictive criteria of further evolution. RESULTS: Among 101 patients referred for surgical resection of incidentally discovered suspected LGG in our center, 19 patients (18.8%) had nonevolutive MRI lesions after a mean follow-up of 46.9 ± 34.9 mo. Insular topography ( P = .003), higher mean volume at discovery (19.2 vs 5.2 cm 3, P < .001), and adjacent sulcal effacement ( P = .001) were associated with evolutive lesions. Histopathological diagnosis of LGG was confirmed in all surgical cases. CONCLUSION: Increasing volume is an effective predictor of LGG diagnosis in incidental MRI findings, as all patients who subsequently underwent surgery had confirmed histopathological diagnosis of diffuse glioma. Approximately 18.8% of incidental findings were stable over time. Insular topography, adjacent sulcal effacement, and volume greater than 4.5 cm 3 were predictive of further radiological progression. These significant elements will help neurosurgeons to define personalized strategies in this complex setting of incidental discovery.